Pathogenetic Mechanism of Type 2 Diabetes Mellitus and its Clinical Implications - Dharmalingam, Mala; Marcus, Sara Rani (Annals of the National Academy of Medical Sciences (India), 2019)
Oxidative stress is an important pathogenetic mechanism for the development of type 2 diabetes mellitus (T2DM) and its complications. Oxidative stress is an imbalance of the generation of free radicals (reactive oxygen species [ROS] and reactive nitrogen species [RNS]) and their neutralization by the antioxidant mechanisms. Increased levels of ROS and RNS lead to damage of lipids, proteins, and DNA, ultimately causing the destruction of the islet cells of pancreas through apoptosis. Another important factor in the development of diabetes mellitus and metabolic syndrome is inflammation. We studied oxidative stress in type 2 diabetic patients, patients with obesity, metabolic syndrome, and T2DM with iron-deficiency anemia. The elevation of oxidative stress in these conditions along with the increase in inflammation suggests that both oxidative stress and inflammation may heighten the risk for the development of T2DM and its complications.
Keywords: oxidative stress; diabetes mellitus; obesity; anemia